Environmental exergonomics for sustainable design and analysis of energy systems. (August 2015) - Golberg, Alexander
Abstract: Exergy analysis methods place a major emphasis on technological and economical optimization of energy systems but have limited ability to address their environmental impacts. Although several approaches, such as Extended Exergy Accounting and Exergonomics, have been proposed to include pollution costs in the energy system optimization, environmental impacts of energy systems are much more complex, as energy systems affect the entire eco-systems services in the areas they are installed. Therefore, energy systems should minimize the adverse impacts on the surrounding eco-system services. In this paper we introduce a method for analysis and optimization of energy systems using technological, economic, and environmental exergy flows. For environmental exergy flow analysis, we included the eco-exergy component in the system objective function. Eco-exergy provides a Second Law derived measurement of the eco-system ability to do work. The disruption of eco-system services, such as reduction of biodiversity, is reflected in a reduction of eco-exergy. Therefore, we propose to include the minimization of the eco-exergy losses in the sustainable energy systems optimization. To demonstrate the method, we analyzed the eco-exergy losses associated with the reduction of the birds' biomass in the EU (European Union) fields dedicated to renewable energy systems. Specifically, we show that the EU renewable energy installations in 2008 lead to addition, today unaccountable, 5 PJ exergetic losses associated with the reduction in the biodiversity and biomass. Highlights: Energy systems sustainability analysis. The contribution of ecological systems exergy to the energy system efficiency. Ecological impacts of large-scale renewable energy systems. Bioenergy and biomass sustainability.